Air Quality Measurements and Education: Improving Environmental Awareness of High School Students - Höfner, Sebastian; Schütze, Andreas (Frontiers in Sensors, 2021)
Indoor air quality (IAQ) has gained renewed importance in public awareness, especially in times of the corona pandemic. In classrooms in particular, regular ventilation is essential to keep the potential viral load in the air as low as possible and thus reduce the likelihood of infection with the corona virus. But also the concentration of other pollutants, such as particulate matter (PM) or volatile organic compounds (VOCs), which are responsible for symptoms such as concentration disorders, headaches and dizziness can be reduced. In addition to the direct measurement of VOC pollutants using metal oxide semiconductor (MOS) gas sensors, CO2 is also measured as an indicator gas for monitoring IAQ. However, young people in particular have only a diffuse idea of air pollutants. This can be explained by the fact that many of these air pollutants are both odourless and colourless and are only detectable using suitable sensors. In order to provide students with a comprehensive picture of the topic of air quality and thus strengthen their environmental awareness, declarative, conceptual and procedural knowledge needs to be combined. This includes knowledge about different sensor principles, pollutant types, their limits, health effects on humans and strategies to maintain good air quality, both indoors and outdoors. To ensure that this knowledge does not remain inert, authentic learning scenarios with a direct relevance to everyday life must be provided. Measuring pollutants in indoor air in particular offers the opportunity to apply what has been learned in a context-oriented manner. By linking the performance of measurements with sensors and the subsequent interpretation of measurement results, environmental awareness can be sharpened with regard to IAQ. This can be achieved by measuring pollutants with sensors and then interpreting and classifying the measurement results. In this paper, various student experiments with gas sensors are presented that introduce the function principles of different sensor types, record air quality data and provide meaningful interpretation. Based on these experiences, students are encouraged to develop their own research questions on air quality.